2021
DOI: 10.1021/acs.energyfuels.1c00181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Chemical Structure of Alkyl Acrylates on Their Defoaming Activity in Crude Oil: Experimental and Theoretical Studies

Abstract: The study and development of non-silicon-based defoamers for crude oils have been slightly investigated worldwide, despite urgent requirements of the petroleum industry. The suppression of crude oils has usually been resolved using commercial silicone defoamers (polysiloxanes), but these compounds cause serious problems such as catalyst poisoning in petroleum refining processes. In this study, an acrylic homopolymer series with different molecular structures was synthesized by emulsion polymerization, to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…By far, the most common and effective defoaming agents are silicone-based products, especially polydimethylsiloxane (PDMS) or fluorosilicone products [ 30 ]. The application of silicone-based compounds in the separation tank can inhibit the formation of foam but can then cause serious catalyst deactivation in the later stage of the refining process [ 53 ]. Therefore, silicone defoaming agents have a good ability to eliminate foam, but the effect of long-term foam inhibition is poor.…”
Section: Discussionmentioning
confidence: 99%
“…By far, the most common and effective defoaming agents are silicone-based products, especially polydimethylsiloxane (PDMS) or fluorosilicone products [ 30 ]. The application of silicone-based compounds in the separation tank can inhibit the formation of foam but can then cause serious catalyst deactivation in the later stage of the refining process [ 53 ]. Therefore, silicone defoaming agents have a good ability to eliminate foam, but the effect of long-term foam inhibition is poor.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that polyacrylates prepared via semicontinuous emulsion polymerization could be applied as defoaming agents to substitute the use of polydimethylsiloxane which is typically used for suppressing foaming in crude oil/gas separation tanks. 64,65 They also reported the employment of terpolymers (polystyrene-polybutylacrylate-polyvinylacetate) as flow improvers for Mexican crude oil and its synthesis was performed in an organic solvent (toluene). 66,67,68 To get a better understanding on the ability of the prepared HAWSP to be applied as flooding agent in the recovery process of a heavy crude oil from a carbonated reservoir located at southern of México, three laboratory tests: contact angle, compatibility, and asphaltene dispersions were carried out using a mixture of heavy crude oil and an aqueous polymer solution at a specific concentration (see Figure 1c).…”
Section: Laboratory Test Of Synthesized Versus Crude Oil Samplementioning
confidence: 99%
“…Vázquez et al reported the use of polymers as defoaming agents for heavy crude oil. They demonstrated that polyacrylates prepared via semicontinuous emulsion polymerization could be applied as defoaming agents to substitute the use of polydimethylsiloxane which is typically used for suppressing foaming in crude oil/gas separation tanks 64,65 . They also reported the employment of terpolymers (polystyrene‐polybutylacrylate‐polyvinylacetate) as flow improvers for Mexican crude oil and its synthesis was performed in an organic solvent (toluene) 66,67,68 …”
Section: Laboratory Test Of Synthesized Versus Crude Oil Samplementioning
confidence: 99%